A wager to win the debutante - Shepherd, Eva (Harlequin historicals., 2024)
All bets are off in this lively Victorian romance full of spice and wit! May the best gentleman win A debutante? Wealthy rail baron Thomas Hayward needs a duke's land to expand his empire, but the oaf insists on a ridiculous wager: they'll both woo debutante Miss Grace Lowerby, and if she chooses the duke-which she surely will-Thomas gets the land at a cheaper price. He can't lose To save her family, Grace must marry the duke. And yet in dashing Thomas she's found a man she can finally be herself with. But focusing on her goal is paramountuntil she discovers the wager and-annoyingly!-that it's Thomas she's falling for!